The Impact of Financial, Psychological, and Social Motivation on Employee Performance Accountability in the Cooperative and SME Office of Klaten Regency - Estiningtyastuti Estiningtyastuti; Simon Nisja Putra Zai; Tulus Prijanto; Rining Dyah Tri Hastuti (PT. Anagata Sembagi Education, 2024)
The objective of this research is to examine the influence of financial, psychological, and social motivation on employee performance accountability within the Cooperative and SME Agency of Klaten Regency. The study encompasses a total employee population of 230 individuals, among whom 64 have less than 5 years of work experience. The research employs Multiple Linear Regression Analysis as its methodology. The results indicate a positive effect of financial motivation on performance accountability, with psychological factors also demonstrating a significant positive impact. Conversely, social factors do not show a significant influence on performance accountability. Therefore, further research is necessary in the areas of psychology and finance, focusing on aspects such as work culture, organisational culture, and the implementation of internal control policies, to enhance employee performance accountability. This study aims to provide deeper insights into the factors affecting performance accountability and to offer valuable recommendations for improving employee performance based on the research findings.